2008
DOI: 10.1111/j.1750-3841.2008.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of California Grown Almonds

Abstract: Eight almond (Prunus dulcis L.) cultivars from 12 different California counties, collected during crop years 2004 to 2005 and 2005 to 2006, were extracted with petroleum ether. The extracts were subjected to GC-MS analyses to determine fatty acid composition of soluble lipids. Results indicated palmitic (C16:0), oleic (C18:1), linoleic (C18:2), and alpha-linolenic (C18:3) acid, respectively, accounted for 5.07% to 6.78%, 57.54% to 73.94%, 19.32% to 35.18%, and 0.04% to 0.10%; of the total lipids. Oleic and lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
75
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 29 publications
(46 reference statements)
18
75
3
Order By: Relevance
“…Oil content in almond kernel shows a high heritability value of 57% [28], confirming that the genetic factor is the most determinant for oil content in almond kernels. This trait appears to be under polygenic control with a clear environmental effect [24,[29][30]. Kodad et al [23] indicated that the magnitude of the effect of the external factors such as the climatic condition of the year probably depends on the genetic background of each cultivar, explaining the significant effect of the interaction genotype X year.…”
Section: Resultsmentioning
confidence: 99%
“…Oil content in almond kernel shows a high heritability value of 57% [28], confirming that the genetic factor is the most determinant for oil content in almond kernels. This trait appears to be under polygenic control with a clear environmental effect [24,[29][30]. Kodad et al [23] indicated that the magnitude of the effect of the external factors such as the climatic condition of the year probably depends on the genetic background of each cultivar, explaining the significant effect of the interaction genotype X year.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently studied relationship is the oleic/linoleic ratio because of its nutritional importance, which shows a wide range of variation depending on the considered author; from 1.96 to 3.05 (Saura et al, 1988), from 2.35 to 6.56 (Kodad, 2006) or from 1.8 to 3.8 (Sathe et al, 2008). The correlation observed in both fatty acids is very high and negative, with r values from −0.92 (Askin et al, 2007) to −0.99 (Sathe et al, 2008).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…They appear in low quantities but have a major influence on almond quality. The proportion of this compound changes according to the cultivar and the kind of cultivation (Prats, 2000;Sathe et al, 2008;Yada et al, 2011;Kodad et al, 2014).…”
Section: Almond: a Nut With High Comercial And Nutritional Valuementioning
confidence: 99%
See 1 more Smart Citation
“…To benefi t more effi ciently from these fruits, the seeds of which are consumed, more information regarding their storage and the developmental characteristics of the cultivars is required [Femenia et al, 1995]. After a long-storage period and transportation, stone fruits undergo extensive fatty acid oxidation and thus their quality signifi cantly decreases [ Recently, some studies were published about total oil and fatty acid profi le of some almond cultivars [Abdallah et al, 1998;Sathe et al, 2008;Özcan et al, 2011;Beyhan et al, 2011]. However, we did not encounter any research on fatty acid profi le in some cultivars such as Desmayo Largueta, Ferrastar, Glorieta, Lauranne, Supernova.…”
Section: Introductionmentioning
confidence: 99%